St. Kitts and Nevis : First Review Under the Stand-By Arrangement and the Financing Assurances Review, and Request for Waivers of Applicability and Modification of Performance Criterion: Staff Report and Press Release. (IMF Staff Country Reports; Country Report, 2012)
The staff report for St. Kitts and Nevis' first review under the Stand-By Arrangement and the Financing Assurances Review is presented. Economic activity is estimated to have been flat in 2011, as continued weakness in the construction sector offset the moderate recovery in tourism and manufacturing sectors. The external current account deficit is estimated to have widened in 2011, with higher energy and food prices more than offsetting the impact of fiscal consolidation and growth in stay-over tourist arrivals.